DISKURSUS PENDIDIKAN ANAK USIA DINI: (Telaah Konsep Pemikiran Pendidikan Jalaluddin Rahmat) - Mustofa, Edy; Nabil, Nabil (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2022)
Islam as a teaching that is universal and applies throughout the ages not only regulates the affairs of the hereafter, but also the affairs of the world. Similarly, Islam regulates the sciences related to God and the sciences related to the worldly. Islam regulates both in an integrated manner. In the Qur'an and as- Sunnah there is actually no term religious science and general science, there is only knowledge itself and all of it comes from Allah SWT. We should support the effort to